A Ovarian Serous Cyst Adenocarcinoma Presented as Post-Menopausal Bleeding - Ahmed, Qumrun Nassa; Nahar, Kamrun; Roy, Joyasree; Shompa, Lima; Akther, Kazi Foyeza; Sultana, Husne Jahan; Sultana, Rifat (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
The various malignant forms of epithelial tumors of the ovary, in practice, are usually grouped together as ovarian adenocarcinoma. These tumors tends to occur in women aged 45-60 years and are commonly asymptomatic until they are achieved a considerable bulk: most common complaints are of increasing abdominal girth, lower abdominal pain or discomfort and the presence of pelvic mass. Urinary symptoms due to pressure on bladder are quite frequent while disturbance of menstrual cycle or post-menopausal bleeding are unusual. Here we present a case of a 60 years old postmenopausal lady with the complaints of post-menopousal bleeding, and heaviness & lump in the lower abdomen. She was clinically diagnosed as a case of ovarian tumor (ovarian malignancy) & went through laparotomy followed by surgical staging. Then TAH with BSO with infracolicomentectomy with pelvic lymphadenectomy was done. Histopathology revealed serous cyst adenocarcinoma (left ovary) without any metastasis to the opposite ovary or any other organs. In our case one of the most common ovarian neoplasm presented with the rarest symptom made the case interesting to report. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 42-44